Potential Development of Goat Farming Business in Kontunaga Subdistrict, Muna Regency - Yani, Wa; Hadini, Hairil A; Aku, Achmad Selamet; Pagala, Muhammad Amrullah (Pascasarjana Universitas Halu Oleo, 2024)
Livestock business development is carried out with reference to regional potential. This research aims to determine the potential for developing goat farming in Kontunaga District, Muna Regency. The research method used is a survey method and direct observation in the field. The location was determined deliberately. The number of respondents in this study was 50 people, taking 10 village breeders in 5 villages that had a goat population. Data sources are primary data and secondary data. Data analysis used descriptive analysis to describe the potential of the region and goat farming business. The results of the research show that the Kontunaga District area has the potential to be used as a goat livestock development area. Breeders are mostly of productive age, 6-10 years of experience, awareness of buying seeds and marketing directly.